Literacy matters in marketing. Issue 5 (3rd July 2017) - Huhmann, Bruce A.
Abstract : Purpose: Literacy represents one's ability to process and produce materials related to a domain. One type of this higher-order, global individual difference variable is consumer financial literacy. It stems from one's financial information processing capacity, prior financial knowledge, and proficiency in optimizing financial decisions and managing financial resources. The paper aims to discuss these issues. Design/methodology/approach: The research matching perspective theoretically explains findings related to literacy, including those in this special issue. Optimal processing arises as available and required processing resources correspond. Thus, cognitive comprehension and behavioral application/decision-making outcomes following financial marketing communication exposure are optimized when consumer financial literacy matches the level needed for successful processing. Insufficient or excess available resources harm outcomes. Findings: The resource-matching perspective clarifies consumers' increasing financial difficulties. Consumers limit personal finance efforts because required resources overwhelm limited financial literacy. However, education or experience can expand consumer financial literacy. Alternatively, financial service marketers may accommodate low consumer financial literacy by simplifying financial information presentation. Consumers reward firms that show sensitivity to their domain-specific literacy limitations with stronger loyalty. Research limitations/implications: Construct definition is vital to advance research. Yet, financial literacy has no generally accepted definition. This paper's definitions should aid understanding of the psychological underpinnings of financial literacy's components. Originality/value: Much has been written about consumers' inability to manage personal finances. This paper provides a unified, theoretical explanation for consumers increasing financial literacy difficulties and suggests ways that consumers, financial service providers, and public policy makers can overcome these difficulties.